Novel Small Molecule Hsp90/Cdc37 Interface Inhibitors Indirectly Target K-Ras-Signaling - Siddiqui Farid Ahmad; Parkkola Hanna; Vukic Vladimir; Oetken-Lindholm Christina; Jaiswal Alok; Kiriazis Alexandros; Pavic Karolina; Aittokallio Tero; Salminen Tiina A.; Abankwa Daniel (MDPI, 2022)
Simple SummaryThe correct folding of proteins is essential for their activity. Therefore, cells have evolved protein-folding chaperones, such as Hsp90. Interestingly, in several cancer cells, Hsp90 appears to have a role that is more important than normal. The current working model suggests that, with the help of its co-chaperone, Cdc37, it stabilizes mutant kinases. However, Hsp90, together with Cdc37, assists additional proteins that may be relevant in cancer. We demonstrate that the Hsp90-dependent stability of the transcription factor HIF-1 alpha and one of its downstream transcriptional targets, galectin-3, is important to maintain the elevated activity of the major oncogene KRAS. This is because galectin-3 stabilizes the MAPK-signaling complexes of K-Ras, which is called a nanocluster. In addition, we identified six drug-like small molecules that inhibit the Hsp90/Cdc37 protein interface at low micro molar concentrations. Given the co-occurrence of mutant KRAS with high HIF-1 alpha and high galectin-3 levels in pancreatic cancer, our results suggest an application of Hsp90 inhibitors in this cancer type.The ATP-competitive inhibitors of Hsp90 have been tested predominantly in kinase addicted cancers; however, they have had limited success. A mechanistic connection between Hsp90 and oncogenic K-Ras is not known. Here, we show that K-Ras selectivity is enabled by the loss of the K-Ras membrane nanocluster modulator galectin-3 downstream of the Hsp90 client HIF-1 alpha. This mechanism suggests a higher drug sensitivity in the context of KRAS mutant, HIF-1 alpha-high and/or Gal3-high cancer cells, such as those found, in particular, in pancreatic adenocarcinoma. The low toxicity of conglobatin further indicates a beneficial on-target toxicity profile for Hsp90/Cdc37 interface inhibitors. We therefore computationally screened >7 M compounds, and identified four novel small molecules with activities of 4 mu M-44 mu M in vitro. All of the compounds were K-Ras selective, and potently decreased the Hsp90 client protein levels without inducing the heat shock response. Moreover, they all inhibited the 2D proliferation of breast, pancreatic, and lung cancer cell lines. The most active compounds from each scaffold, furthermore, significantly blocked 3D spheroids and the growth of K-Ras-dependent microtumors. We foresee new opportunities for improved Hsp90/Cdc37 interface inhibitors in cancer and other aging-associated diseases.